Service offshoring: A challenge for employment? Evidence from Germany - Deborah Schöller (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2007)
Besides material offshoring, economists have started to analyze the impact of service offshoring on domestic employment. Services are of particular interest since their significance has grown not only in terms of quantity, but also of qualitative understanding. One decade ago, most services were considered non-tradable, but the appearance of new information and communication technologies has contributed to overcoming geographical distance. The introduction of the paper aims at giving an appropriate definition of service offshoring also taking into account the different motives behind offshoring. The theoretical part gives a brief literature overview of the predicted effects of offshoring on domestic employment. The empirical part first compares import data of computing and information as well as other business services and states that service offshoring is more relevant in Germany than in most other countries. Secondly, German service offshoring intensities are calculated on a sectoral basis using input-output data. This measurement represents the proportion of imported service inputs used in home production. Germany's average service offshoring intensity more than doubled from 1991 to 2002. Besides this, indications for a possible negative correlation between German service offshoring and manufacturing employment are given. Thirdly, the impact of service offshoring on German domestic manufacturing employment is estimated at a sectoral level. The author refers to the labor demand specification of Hamermesh using sectoral wages, output and other input prices as exogenous variables. The estimation results indicate that service offshoring was negatively related to manufacturing employment in Germany between 1991 and 2000.
Keywords: F1; F2; 330; service offshoring; employment; globalization; Offshoring; Unternehmensdienstleistung; Beschäftigungseffekt; Deutschland